(untitled) (International Journal of Banking and Finance, 2024)
Firms’ decisions are not independent of their peers. This study aims to assess the impact of peer pressure on firms’ dividend policy. In a sample of 29 firms from 2014–2020, this study employed a fixed effect regression model and revealed that Bangladeshi firms adjusted their dividend policy in response to their peers. Firms adjust the dividend payout ratio (DPR) by 5.6 percent as a response to their peers. Social learning theory, reputation-based model of peer influence, persuasion bias and rivalry-based theory of mimicking explain how peer influence affects a firm’s dividend policy. The findings of positive peer effects on dividend policy are robust to an alternative proxy of dividend policy – dividend yield. Therefore, the study implied that managers’ decisions regarding the dividend policy are not independent of their peer firms. Investors can adjust their expectations of a firm’s dividend policy based on the overall dividend policy in the industry.